Male meiotic cytokinesis requires ceramide synthase 3-dependent sphingolipids with unique membrane anchors - Rabionet Roig, Mariona; Porubský, Štefan (Human molecular genetics, 2015)
Somatic cell cytokinesis was shown to involve the insertion of sphingolipids (SLs) to midbodies prior to abscission. Spermatogenic midbodies transform into stable intercellular bridges (ICBs) connecting clonal daughter cells in a syncytium. This process requires specialized SL structures. (1) Using high resolution-mass spectrometric imaging, we show in situ a biphasic pattern of SL synthesis with testis-specific anchors. This pattern correlates with and depends on ceramide synthase 3 (CerS3) localization in both, pachytene spermatocytes until completion of meiosis and elongating spermatids. (2) Blocking the pathways to germ cell-specific ceramides (CerS3-KO) and further to glycosphingolipids (glucosylceramide synthase-KO) in mice highlights the need for special SLs for spermatid ICB stability. In contrast to somatic mitosis these SLs require ultra-long polyunsaturated anchors with unique physico-chemical properties, which can only be provided by CerS3. Loss of these anchors causes enhanced apoptosis during meiosis, formation of multinuclear giant cells and spermatogenic arrest. Hence, testis-specific SLs, which we also link to CerS3 in human testis, are quintessential for male fertility.